Digital Transformation in Transportation Management at PT Pos Logistik Indonesia - Adriansyah Nugraha (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2025)
The advancement of information technology has transformed the role of transportation management from a supporting operational function into a strategic component that enhances efficiency and effectiveness in logistics operations. This study aims to analyze the implementation of a web-based transportation management system at PT Pos Logistik Indonesia and to evaluate the system’s impact on operational performance and organizational competitiveness. Using a qualitative descriptive method, data were collected through observation, semi-structured interviews, and documentation review. The results indicate that the implementation of the system improves fleet management efficiency by optimizing maintenance schedules, reducing operational costs, increasing asset control accuracy, and improving occupational safety. Moreover, the integration of digital technology facilitates faster and more accurate decision-making through real-time data visibility. Despite these advantages, several challenges remain, including dependency on Excel-based systems and limited automation. Overall, the study concludes that digital transformation in transportation management plays a strategic role in supporting operational excellence and long-term competitiveness at PT Pos Logistik Indonesia.